Correction: Diagnosis challenges and accessibility barriers to migraine management in Southeast Asia: results from the South-East Asia Local breAch on MigraiNe Treatment (SEALANT) study (The Journal of Headache and Pain, (2026), 27, 1, (47), 10.1186/s10194-026-02295-1) - Rattanawong, Wanakorn; Hiransuthikul, Akarin; Anukoolwittaya, Prakit; Pongpitakmetha, Thanakit; Thanprasertsuk, Sekh; Manohararaj, Nijanth; Sulaiman, Wan Aliaa Wan; Saranza, Gerard; Wee, John Luis; Dayrit, Greg; Madjid, Irma Savitri; Sudibyo, Devi Ariani; et al. (My University, 2026)
In the section Survey and outcomes of this article, the components of the questionnaire were incorrectly labeled using the manuscript-style headings “Introduction,” “Methods,” “Results,” “Discussion,” and “Conclusion.” These terms were intended solely to denote internal sections of the questionnaire and do not correspond to the standard structural sections of the manuscript. To avoid confusion, these labels have been replaced with “Section 1,” “Section 2,” “Section 3,” “Section 4,” and “Section 5,” respectively. The correct and incorrect version of the text is presented below and the original article has been corrected. The survey comprised five main sections, each designed to explore different aspects of migraine care and physician perspectives. Section 1 collected demographic data. Section 2 focused on barriers to migraine diagnosis, covering issues such as diagnostic accuracy, time to diagnosis, hospital workload, and use of headache diaries and patient education. Section 3 explored acute migraine treatment, including medication availability, the proportion of patients using acute medications, issues of medication underuse (timing and efficacy), and awareness of MOH. Section 4 explored preventive treatment, including access to preventive medications, availability of calcitonin gene-related peptide (CGRP)–targeted therapies, and physicians’ views on their use. Section 5 explored migraine-related stigma and its impact on patients’ quality of life; these findings will be reported separately. The survey comprised five main sections, each designed to explore different aspects of migraine care and physician perspectives. Section “Introduction” collected demographic data. Section “Methods” focused on barriers to migraine diagnosis, covering issues such as diagnostic accuracy, time to diagnosis, hospital workload, and use of headache diaries and patient education. Section “Results” explored acute migraine treatment, including medication availability, the proportion of patients using acute medications, issues of medication underuse (timing and efficacy), and awareness of MOH. Section “Discussion” explored preventive treatment, including access to preventive medications, availability of calcitonin gene-related peptide (CGRP)–targeted therapies, and physicians’ views on their use. Section “Conclusion” explored migraine-related stigma and its impact on patients’ quality of life; these findings will be reported separately.